IMPLEMENTASI E-KATALOG DALAM PENGADAAN BARANG DAN JASA DI PEMERINTAH KOTA SEMARANG - Ramadhani, Dewi; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2025)
This study aims to examine the implementation process of E-Catalog in government procurement of goods and services in the Semarang City Government and to identify the supporting and inhibiting factors encountered in the implementation of E-Catalog in government procurement of goods and services in the Semarang City Government. This research employs a qualitative method with a descriptive approach. Data was collected through interviews, observations, and documentation. The results of this study indicate that the implementation of E-Catalog in the procurement of goods and services in the Semarang City Government has not been optimal due to existing constraints in the dimensions of Fairness and Competition. However, the dimensions of efficiency, effectiveness, transparency, openness, and accountability are already functioning well. There are supporting factors for the implementation of E-Catalog in the procurement of goods and services in the Semarang City Government, including communication and resource factors, while the inhibiting factors for the implementation of E-Catalog in the procurement of goods and services in the Semarang City Government are disposition factors and bureaucratic structure. Recommendations from this research are divided into internal factors, which are expected to implement a comprehensive input collection system, and external factors can be carried out by forming a specialized team tasked with socialization and providing technical assistance to providers.